What Influences the Victimization of High-Level Offenders? A Dual Trajectory Analysis of the Victim–Offender Overlap From the Perspective of Routine Activities With Peer Groups. Issue 17 (September 2021) - Erdmann, Anke; Reinecke, Jost
Although the consistent association between offending and victimization is a long-noted phenomenon, current criminological research is still engaged to gather profound knowledge on the etiology of this victim–offender overlap. Beyond that, the examination of its development over the life course requires further attention to create a better understanding of why offending and victimization are strongly connected. Applying a joint trajectory technique, the present study examines the overlap between distinct trajectories of offending and violent victimization throughout the phase of youth and adolescence using seven consecutive waves from the German longitudinal study "Crime in the Modern City." In particular, the victimization of high-level offenders is investigated taking a routine activity perspective with a focus on activities with peers. The results indicate that there is a sizable overlap between trajectories of violent victimization and constant offending with four out of five high-level offenders being repeatedly victimized. Furthermore, the examination shows that meeting more frequently with friends, going out and drinking alcohol, doing forbidden things for fun, and casually hanging out with friends increases the risk of high-level offending significantly. Moreover, the analysis indicates that meeting frequently with friends enhances the risk of violent victimization for offenders, whereas casually hanging out reduces the risk. However, these impacts can only be observed for the present sample and cannot be generalized with sufficient certainty. In addition, the analysis provides evidence that gender differences in the victim–offender overlap are mediated through diverging activities. Implications and limitations are discussed.